The Utilization of end-of-Life Tire Fragments Rubber in Concrete, in Place of Sand Aggregate - Kuldashev Kh.; Qo’ziboyev A.; Mannatov B.; Ortiqov Sh., (European Journal of Life Safety and Stability (2660-9630), 2023)
The use of reclaimed tires in civil engineering practices, specifically asphalt paving mixtures and cement-based materials, is gathering traction throughout the globe. This article provides a comprehensive summary and comparison of recent accomplishments in the field of ordinary rubberized concrete (PRC). Different treatment methods to enhance the efficacy of rubberized Portland cement concrete have been discussed. The analysis also contains the effects of tire rubber size and quantity on the mechanical and durability properties of PRC. The behavior of the rubberized concrete's microstructure was elaborated.